Preparation and Functional Properties of Hydroxy-propylated Sweet Potato (Ipomoea batatas L.) Starch - Ogundiran Abimbola Aina; Ayisat Temitayo Tijani; Olusegun Olafimihan Ogundiran; Oyesolape Basirat Akinsipo; Ali El Gamal; Talha Bin Emran; Mohamed Hefnawy (BioResources)
Sweet potato (Ipomoea batatas L.) is an underutilized tuber in Nigerian industries. Its starch has diverse culinary and non-food applications. In this study, locally sourced sweet potato starch was isolated and hydroxypropylated using propylene oxide. The percentage of hydroxypropyl groups added and the degree of substitution were determined. Functional groups and morphological characteristics of both native and modified starches were analyzed using FT-IR and scanning electron microscopy (SEM). Functional and pasting properties were also examined. The degree of substitution and hydroxypropyl content fell within acceptable food application limits. SEM showed that granule structure remained intact after surface modification. Hydroxypropylated starches exhibited higher swelling and solubility than native starch from 50 to 90 °C. Both properties increased with greater molar substitution. Hydroxypropylation reduced storage turbidity and syneresis. Peak viscosity increased, while pasting and peak temperatures decreased after modification. Hydroxypropylated starches also had lower setback values. These results indicate enhanced functional properties in modified starch. The modified starch showed industrial potential for use in confectioneries, salad cream, mayonnaise, as well as in roles such as texturizers, thickeners, stabilizers, fillers, flavor carriers, and ingredients in beverages and bakery products, all with energy-efficient processing advantages.